AquaNet - Manual sonde from Bolmen, mesocosm, 2022-07-07–2022-08-12 - Bolmen Research Station (Swedish University of Agricultural Sciences, 2026)
Manual sonde data from the AquaNet mesocosm facility
Bolmen Research Station (2026). AquaNet - Manual sonde from Bolmen, mesocosm, 2022-07-07–2022-08-12 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/bVloR08OIWBvmkI3ObtFiUf2
Keywords: SITES AquaNet; Conductivity; Turbidity; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap